Microsurgical Neurovascular Anatomy of the Brain: The Anterior Circulation (Part I) - Giotta Lucifero, Alice; Baldoncini, Matias; Bruno, Nunzio; Tartaglia, Nicola; Ambrosi, Antonio; Marseglia, Gian Luigi; Galzio, Renato; Campero, Alvaro; Hernesniemi , Juha; Luzzi, Sabino (Acta Biomedica Atenei Parmensis, 2021)
Introduction Treatment of cranial neurovascular pathology requires a detailed understanding of the brain, head, and neck vasculature.This study aims at a comprehensive overview of the microsurgical anatomy of the anterior cerebral circulation.MethodsFive formalin-fixed adult cadaveric heads were used. Common carotid arteries, vertebral arteries, and internal jugular veins were injected with colored latex (red for arteries and blue for veins). The heads were dissected under a surgical microscope with magnifications ranging between 3× to 40× focusing on the anterior circulation. A synoptic approach was used to describe in detail the segments, branches, perforating arteries, veins, and vascular territories of the cerebral arteries and veins.ResultsThe anterior arterial circulation of the brain is provided by the internal carotid artery (ICA), anterior cerebral artery (ACA), middle cerebral artery (MCA), anterior communicating artery (ACoA), and perforating arteries. Perforating arteries of the anterior circulation arise from the ICA, ACA, MCA, ACoA, and posterior communicating artery (PCoA). The distal segments and collateral branches of the ICA, ACA, and MCA give the arterial supply to the largest part of the forebrain, whereas perforating arteries of the anterior circulation are related to the striatum, thalamus, and basal ganglia. The ACoA is the core functional anastomosis between the left and right ICA systems. The external carotid artery provides the vascular supply to the region of the face, head, and neck, and most of the meninges. The internal jugular venous system is composed of the internal and external jugular veins, which constitutes the outflow of the cerebral and facial venous system, respectively.ConclusionThorough knowledge of the topographic, cisternal, and functional anatomy of the anterior circulation of the brain is critical for surgery of the supratentorial lesions.